Actual Coverage of the Funds on the Account by the Order About the Evidence - Samiczak, Kamil; Jaworski , Damian Robert (NBP. Nauka, bezbednost, policija, 2024)
SUMMARYThe subject of this article is consideration of recent changes in the criminal procedure in force. These are two resolutions of the Supreme Court of October 13, 2021, ref. no. no. I KZP 1/21 and of November 9, 2021, ref. no. act I KZP 3/21. After their issuance, the Act of 17 December 2021 amending certain acts in connection with the establishment of the Central Bureau for Combating Cybercrime (Journal of Laws of 2021, item 2447), Art. 236b, which makes the cited resolutions outdated. Instead of a blockade, the funds on the account may be actually covered by recognizing them as evidence, but this should only take place in the event of the ultima ratio, i.e. after the maximum duration of the transaction suspension or account blocking period has been exhausted, with simultaneous impossibility of using property collateral. This possibility applies to both fiat and virtual currencies.